Utilization of livestock manure based biogas for climate change mitigation in Nakuru county, Kenya (Journal of Sustainability, Environment and Peace, 2019)
ABSTRACT Burning of wood fuel degrades forests, causes indoor household air pollution and releases greenhouse gases contributing to deforestation and climate change. Livestock manure decomposes anaerobically producing greenhouse gases. Comparative study of wood fuel usage and Methane emissions from wood stove user households and biogas cook-stove user households was conducted in Nakuru County, Kenya. The study aimed at determining the wood fuel and biogas usage in households of Nakuru County and estimating reduced wood fuel usage and Methane emissions amounts from use of biogas as a way of mitigating climate change. The study also, examined how biogas use contributes to the improvement of household livelihoods. One hundred and twenty one dairy cattle farmer households (HHs) were clustered into 5 regions and purposively sampled into wood stove user households and biogas cook-stove user households. The study used survey research design where data was collected using questionnaire and key informant interview. Results indicated that mean annual wood fuel usage for wood stove user HHs and biogas cook-stove user HHs was equivalent to 14 and 7 mature trees respectively. The mean biogas usage for biogas cook-stove user households was 481.6 m3 per year. Maximum values of Methane emissions from wood stove user households and biogas cook-stove user households were 2048 and 956 KgCO2e/HH/year respectively. It was estimated that about 50-53% of Methane emissions from wood fuel usage can be reduced by using biogas cook-stoves. Reduced wood fuel usage of 3899.4 Kg/HH/year due to biogas use translated to conserving 8 mature trees per household per year. The conserved trees can absorb additional 6433.99 -7018.90 Kg of Carbon dioxide per year. Biogas utilization could therefore be a good option for reducing deforestation and Methane emissions in the context of climate change.
Keywords: Key words: Biogas, Climate change, Emissions, Mitigation, Woodfuel.